Winter behaviour of wild Whistling Swans: a comparison with Bewick's Swans - Scott, D K (Wildfowl, 1980)
A brief study of the behaviour of Whistling Swans Cygnus c. columbianus feeding on agricultural crops was made in Maryland, USA. In the absence of their parents, cygnets suffered increased harassment by other individuals and spent less time feeding. In most aspects of behaviour Whistling Swans were apparently indistinguishable from the conspecific Bewick's Swan C. c. bewickii.